Strategi Mengembangkan Usaha Mikro, Kecil, Menengah (Umkm) di Kecamatan Bangkinang Kota dan Salo - Dzulhijjah Yetti; Rahmad Akbar (Politeknik Kampar, 2022)
Micro, Small, Medium Enterprises or UMKM are a category of small-scale businesses that are believed to be able to contribute to the economy of Kampar Regency. UMKM as a means to create the private sector so that the development of UMKM plays an important role in economic development. According to Law No. 9 of 1995, coaching and development is an effort made by the government, the business world and the community through the provision of guidance and reinforcement assistance to grow and improve the ability of small businesses to become strong and independent businesses and can develop into medium-sized businesses. The purpose of this study was to analyze the development of UMKM in Kampar Regency. The population is UMKM actors and UMKM consumers, the research sample is 98 UMKM actors and 96 UMKM consumers. This research uses the SWOT method. The results show that the SWOT strategy is very helpful for developing UMKM. Keywords— UMKM, Development, SWOT